Customer Loyalty Analysis On Online Travel Agent (OTA) Using American Customer Satisfaction Index (ACSI) And Structural Equation Modelling (SEM) - Yanu Ramdhani Saputra; Herlina Jayadianti; Dyah Ayu Irawati (Telematika, 2022)
Purpose: Knowing what affects customer loyalty in Online Travel Agent (OTA) Services. Which will help OTA Services to understand about customer satisfaction and customer loyalty so that they can develop their business in the future in order to get greater customer satisfaction and loyalty.Design/methodology/approach: Using the American Customer Satisfaction Index (ACSI) Model which explains the antecedents and consequences of customer satisfaction. In Antecedent there are variables of User Expectations, Perceived Quality, and Value benefits that have an impact on customer satisfaction variables then from causing customer complaints and customer loyalty. So that 9 research hypotheses are obtained based on the model used and tested using Structural Equation Modeling (SEM). Research requires data on respondents' answers distributed through digital media with a total need for 385 respondent data.Findings/result: After testing using SEM.The 9 hypotheses proposed show that 2 hypotheses are rejected and 7 hypotheses are accepted.Originality/value/state of the art: Previous research has been done but with different models and different methods.